Child development and nutritional status in 12-59 months of age in resource limited setting of Ethiopia - Shimelash Bitew Workie; Tesfa Mekonen; Tefera Chane Mekonen; Wubalem Fekadu (BMC, 2020)
Abstract Background Early years of life are period of maximal growth and development of human brain. Development of young child is influenced by biological endowment and health of child, nutritional status of child, relationships with primary caregivers, family, and support systems in the community. This study was aimed to assess childhood development in relation to their nutritional status. Method Community-based cross-sectional study was employed. Multi-stage systematic random sampling technique was used to select 626 children aged 12-59 months with mother/caregivers' pairs in Wolaita district in 2015. Child development assessment was done using third edition of age and stage questionnaire. Height and weight were measured by trained data collectors then the WHO Anthro version 3.2.2 software was used to convert nutritional data indices. Data were entered into Epi-info version 3.3.5 and was exported and analyzed using STATA version 14. Correlation and multiple logistic regression were used. Result High risk of developmental problem in children were 19.0% with 95% CI (16.06%, 22.3%), and it is expressed as communication 5.8%, gross motor 6.1%, fine motor 4.0%, personal social 8.8%, and problem solving 4.1%. One-third (34.1%) of the study participants were stunted while 6.9% and 11.9% of them were wasted and underweight respectively. Weight-for-age (WAZ) and height-for-age positively correlated with all five domains of development, i.e., with communication, gross motor, fine motor, personal social, and problem solving (r = 0.1 − 0.23; p < 0.0001, and r = 0.131 − 0.249; p < 0.0001) respectively. Conclusion and recommendation Overall child development was directly related with nutritional status. So, available resources should be offered to decrease children undernutrition. Further assessment on childhood development of children is necessary